Root competition between coconut palms and interplanted multipurpose trees under varying nutrients management regimes - Sanjeev Gowda H B (Department of Silriculture and Agronomy, College of Forestry, 2002)
Coconut based production systems in the tropics often aim at improved resource capture through incorporating several trees and field crops. However, competition between the system components are probable when multipurpose trees are systematically interplanted in the coconut plantations. Soil fertility regimes are presumably important in determining the magnitude of below ground competitive interactions. Hence a study was conducted to evaluate the influence of interplanted multipurpose trees on coconut productivity along a soil fertility gradient, to assess the performance of multipurpose trees and to determine the nature of below ground interactions between coconut palms and multipurpose trees, at Vellanikkara since 1992. Treatments included combinations of cocounut with anyone of the three multipurpose trees namely, Vateria indica, Ailanthus triphysa and Grevillea robusta, following two planting geometries(randomised block design, replicated thrice). A soil fertility gradient, was super-imposed with high, medium and low fertility levels in 2000. 32p soil injection technique was employed to characterize . root interaction and logarithmic spiral trenching technique for evaluating root distribution pattern. Results show that coconut yield was not adversely affected by multipurpose trees interplanting until the trees reached eight years of age. Vateria, ailanthus and grevillea showed marked variations in their growth rates. Initially vateria recorded higher height and radial growth albeit ailanthus registered higher growth rates subsequently.